1998
DOI: 10.1034/j.1399-3054.1998.1020314.x
|View full text |Cite
|
Sign up to set email alerts
|

Freezing tolerance, cold acclimation and oxidative stress in potato. Paraquat tolerance is related to acclimation but is a poor indicator of freezing tolerance

Abstract: Potato is a species commonly cultivated in temperate areas where the growing season may be interrupted by frosts, resulting in loss of yield. Cultivated potato, Solanum tuberosum, is freezing sensitive, but it has several freezing‐tolerant wild potato relatives, one of which is S. commersonii. Our study was aimed to resolve the relationship between enhanced freezing tolerance, acclimation capacity and capacity to tolerate active oxygen species. To be able to characterize freezing tolerant ideotypes, a potato p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…Because many stress conditions provoke cellular redox imbalances, it has been suggested that oxidative stress defenses contribute to induced abiotic and biotic stress tolerance and are a central crosstolerance-mediating component (7). This notion is also supported by the fact that plants acclimated to heat or cold as well as plants showing acquired resistance to pathogens are all more tolerant to oxidative stress (8)(9)(10). Antioxidant defense responses have long been associated mainly with enhanced antioxidant enzyme activity and increased levels of antioxidant metabolites, such as ascorbic acid, glutathione, ␣-tocopherol, and carotenoids (11).…”
supporting
confidence: 49%
“…Because many stress conditions provoke cellular redox imbalances, it has been suggested that oxidative stress defenses contribute to induced abiotic and biotic stress tolerance and are a central crosstolerance-mediating component (7). This notion is also supported by the fact that plants acclimated to heat or cold as well as plants showing acquired resistance to pathogens are all more tolerant to oxidative stress (8)(9)(10). Antioxidant defense responses have long been associated mainly with enhanced antioxidant enzyme activity and increased levels of antioxidant metabolites, such as ascorbic acid, glutathione, ␣-tocopherol, and carotenoids (11).…”
supporting
confidence: 49%
“…Solanum commersonii is known to be the most frost tolerant species of potato together with Solanum acaule [34,35]. Cultivated potato, Solanum tuberosum , is sensitive to freezing [36] and possesses little genetic variation in their tolerance to cold stress [6,37].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, when an independent F 2 progeny from the same somatic hybrid was analyzed for frost tolerance and acclimation capacity, a large variability for both traits was observed, and plants were identified with a better frost tolerance and/or acclimation capacity than that of the somatic hybrid, and close to that of the parental wild species (Seppanen et al 1998). Indeed, our data clearly suggest that the variability observed in an F 2 progeny previously analyzed for various morphological traits ) could be the result not only of segregation but also of recombination between the homoeologous cmm and tbr genomes.…”
Section: Crossing-over Eventsmentioning
confidence: 99%